2018
DOI: 10.1016/j.fertnstert.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the risk of adverse pregnancy outcomes of Chinese patients with polycystic ovary syndrome with and without antiandrogenic pretreatment

Abstract: In our highly selected study population, patients with PCOS are more likely to develop GDM, PIH, and PD. Pretreatment with EE/CPA was associated with a lower risk of GDM, PIH, and PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
(43 reference statements)
0
22
0
1
Order By: Relevance
“…A systematic review demonstrated that features characteristic of PCOS before pregnancy, such as hyperandrogenism, obesity, insulin resistance and metabolic abnormalities, might contribute to the increased risk of HDP 29 . If ethinylestradiol/cyproterone acetate was used as pretreatment for hyperandrogenism among women with PCOS, the risk of GDM, pregnancy‐induced hypertension, and preterm birth was decreased 13 . Although the value of the Rotterdam criteria to guide treatment is controversial, research evidence has shown that the Rotterdam criteria have advantages in predicting reproductive outcomes 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review demonstrated that features characteristic of PCOS before pregnancy, such as hyperandrogenism, obesity, insulin resistance and metabolic abnormalities, might contribute to the increased risk of HDP 29 . If ethinylestradiol/cyproterone acetate was used as pretreatment for hyperandrogenism among women with PCOS, the risk of GDM, pregnancy‐induced hypertension, and preterm birth was decreased 13 . Although the value of the Rotterdam criteria to guide treatment is controversial, research evidence has shown that the Rotterdam criteria have advantages in predicting reproductive outcomes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and biochemical hyperandrogenism were both included in the diagnosis of hyperandrogenism. Clinical hyperandrogenism was indicated by symptoms including hirsutism, acne and androgenic alopecia 13 . Biochemical hyperandrogenism was diagnosed if testosterone exceeded 76 ng/dl according to the reference value of our laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age, with an estimated prevalence of 10% around the world [1] and 5.6% in Chinese women aged 19-45 years [2]. This complex endocrine disturbance reflects multiple variable biochemical and clinical manifestations such as hyperandrogenism (HA), insulin resistance, dyslipidemia, obesity, and frequently with menstrual irregularities, infertility, and increased risk of adverse pregnancy outcomes [3][4][5]. These signs and complications can also lead to psychosocial and emotional disturbances and seriously affect quality of life [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease characterized by menstrual disorder, oligo/anovulation, hyperandrogenemia, polycystic ovaries, and insulin resistance. [ 1 ] Studies [ 2 , 3 ] show that PCOS with complex etiology affects 6% to 15% women of childbearing age, approximately 75% of whom experience infertility due to anovulation. The pathogenesis of PCOS is mostly metabolic disorder caused by insulin resistance and secondary hyperinsulinemia, which can lead to endometrial cancer, cardiovascular disease, type 2 diabetes, and other diseases over time, affecting women's physical, and mental health.…”
Section: Introductionmentioning
confidence: 99%